Penerapan Otomasi Perpustakaan di MA Ma’arif 1 Punggur - Fera Lestari; Erliyan Redi Susanto; Asep Haikal Kurniawan; Dian Pratiwi; Wahyu Saputra (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Abstract: Information technology can be used to support activities in various sectors without exception in the field of education. The teaching and learning process in schools is strongly supported by the availability of facilities. Facilities support students in achieving learning objectives. One of the most important facilities to support learning activities in schools is the library. In its management, library functions can be achieved optimally if there is a system to simplify activities in the library. A good library management management system can certainly improve services in school libraries. One form of information technology application for libraries is library automation. The solution to the problem in the form of library automation is expected to be able to assist librarian in carrying out library management. This library automation can also be an important point in providing school facilities and infrastructure, which in turn can be used for school accreditation.Community service activities for the target school scheme with library automation training activities at MA Ma'arif 1 punggur are the availability of software on computers used in libraries as tools used for library automation with features used in the form of book collections (bibliography), library membership and circulation